2012
DOI: 10.1210/jc.2011-3350
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone, a Glucocorticoid Receptor Antagonist, Produces Clinical and Metabolic Benefits in Patients with Cushing's Syndrome

Abstract: Mifepristone produced significant clinical and metabolic improvement in patients with CS with an acceptable risk-benefit profile during 6 months of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
360
2
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 419 publications
(386 citation statements)
references
References 35 publications
16
360
2
8
Order By: Relevance
“…Results from the SEISMIC (Study of the Efficacy and Safety of Mifepristone in the Treatment of Endogenous Cushing Syndrome) trial reported significant improvements in glycemia in 60% (15/25) of patients with baseline diabetes or glucose intolerance following 24 weeks of mifepristone therapy (23). In addition, the majority of patients with hypertension in this study had either a ≥5 mm Hg decrease in diastolic blood pressure or a reduction in the number of antihypertensive medications following mifepristone treatment.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Results from the SEISMIC (Study of the Efficacy and Safety of Mifepristone in the Treatment of Endogenous Cushing Syndrome) trial reported significant improvements in glycemia in 60% (15/25) of patients with baseline diabetes or glucose intolerance following 24 weeks of mifepristone therapy (23). In addition, the majority of patients with hypertension in this study had either a ≥5 mm Hg decrease in diastolic blood pressure or a reduction in the number of antihypertensive medications following mifepristone treatment.…”
Section: Introductionmentioning
confidence: 58%
“…Centrally acting agents that target excessive pituitary adrenocorticotropic hormone (ACTH) secretion, inhibitors of See accompanying article, p. 1175. steroidogenesis, or glucocorticoid receptor antagonists have been utilized depending on the underlying cause of CS. Prospective clinical trials, however, are limited (22), and there have not been any head-to-head studies comparing the efficacy, tolerability, and safety of the U.S. Food and Drug Administration (FDA)-and non-FDA approved drugs (14,17,23,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reimbursement values for each CPT code (50th percentile) for physician services or outpatient services/procedures/labs were obtained from the MAG Mutual Physicians' Fee and Coding Guide 2012, and were summed separately to generate costs of surgery or radiation therapy. Costs for drug therapies in both scenarios are calculated based on the mean recommended daily dosage for each treatment (obtained from published literature) 2,28,[36][37][38] . Daily drug costs are estimated by multiplying mean daily dose (in mg) with the lowest drug cost per mg that was obtained using the wholesale acquisition cost (WAC) from the 2013 Drug Topics Redbook 39 .…”
Section: Treatment Durationmentioning
confidence: 99%
“…A literature review was conducted and eight studies identified as the most appropriate clinical studies for inclusion in the total budget impact model 37,38,[40][41][42][43][44][45] . Fourteen unique AEs were identified, of which hypopituitarism was associated with TSS, RS, and RT.…”
Section: Surgical Complications and Adverse Eventsmentioning
confidence: 99%